Teacher Skills in Classroom Management in Thematic Learning in Elementary Schools/Keterampilan Guru dalam Pengelolaan Kelas pada Pembelajaran Tematik di Madrasah Ibtidaiyah - Nino Indrianto; Desi Nurul Fatmawati (Al-Mudarris: Journal Of Education, 2020)
In service teachers are required to develop teaching skills as well as skill in managing classroom. The present study aims to explore the skills of the grade IV Islamic primary school teachers in Jember in managing classroom and to figure out the supporting and inhibiting factors emerged in thematic learning. This research employs a qualitative approach with a case study design. Data isgarnered through observation, interviews, and documentation. The results of this study are 1) the skills of fourth grade teachers of Darussalam 01 Islamic primary school are depicted from seating patterns arrangement, thematic decoration arrangement, wall magazines, student work display, learning media display, and the teacher carries out thematic learning with a variety of interesting methods and is able to provide meaningful experiences; 2) Supporting factors which have implications for classroom management include the K13 curriculum integration, teacher creativity, school principal support, student involvement, representative classroom conditions, and student guardian support. The inhibiting factors of class management include the teacher time limitation, the low level of student guardian support, and the low sense of ownership and responsibility of students towards their class.